INOVASI PELAYANAN PUBLIK AJI ARUM (AKTA JADI ANTAR RUMAH) DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SEMARANG DI KECAMATAN KALIWUNGU - Siti Arofah; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
ABSTRACT Various ways are carried out by government agencies so that an effective and efficient service system can be achieved, one of them is by creating innovation. The Semarang Regency Population and Civil Registry Office created an innovative House-to-House Certificate to make it easier for the community to obtain a birth certificate, whose application can now be done in the District. In AJI ARUM's innovation, the Semarang Regency Population and Civil Registry Office collaborated with PT Pos Indonesia to deliver the birth certificate to the applicant's address, the documents obtained were Birth Certificate, new KK and KIA. This study aims to determine the implementation of AJI ARUM's innovation at the Population and Civil Registry Office of Semarang Regency and Kaliwungu District, as well as the factors that are inhibiting the implementation of these innovations. This study uses the theory of innovation characteristics according to M. Rogers which includes relative advantages, compability, complexity, triability and observability. The obstacles faced in the implementation of AJI ARUM's innovations are the lack of enthusiasm of the community in arranging birth certificates and the lack of public understanding of the importance of population administration.